A Comprehensive Review on the Biomarkers of Bone Remodeling in Vitamin D Deficiency - Krishna Veni Nagappan; Arti Sureshkumar (Universitas Gadjah Mada, 2021)
Vitamin D (Vit.D) has been well regarded as one of the essential micronutrients for several biological functions in humans, including bone structure and function. The deficiency of Vit.D due to various environmental, lifestyle, and genetic factors affect bone remodeling, including bone mineralization and resorption. Consequently, several changes occur in the level of biochemicals which are implied in bone remodeling, either directly or via secondary pathways. Intriguingly, the levels of these biomolecules are hypothesized to have a strong association with the prognosis of Vit. D deficiency (VDD) related health complications. However, the precise association of various bone turnover-derived biomolecules with VDD-related effects are largely elusive. Thus, the in-depth understanding of specific associations of VDD and bone mineralization, would establish novel bioanalytical approaches for early detection and devise alternative strategies to provide symptomatic clinical support to VDD patients. Hence this review collates the available literature to elucidate the association of various bone resorption biomarkers and their relevance to VDD.